Características epidemiológicas y clínicas de lactantes con bronquiolitis aguda que nacieron de parto por cesárea. Hospital Belén de Trujillo, 2016 - Morales Ibañez, Manuel Alejandro (2020)
Objective: To identify the epidemiological and clinical characteristics of infants with acute bronchiolitis who were born by caesarean delivery attended at Belén Hospital of Trujillo in 2016. Materials and methods: We worked with 36 clinical records of infants with acute bronchiolitis who were born in caesarean delivery attended at hospitalization service of Belen Hospital of Trujillo during January to December of 2016. We used an observational cross-sectional descriptive design. Results: Regarding epidemiological characteristics, the majority of children presented: Male sex (61.1%), less than 6 months (86.1%), term birth (86.1%), adequate weight at birth (88.9%) and good nutritional status (91.7%) %). Only 8.3% had a history of congenital heart disease and 30.6%, absence of breastfeeding. The month of the year with the highest incidence was June (30.6%). In relation to the clinical characteristics, these were tachypnea (100%), retraction (100%), cough (86.1%), wheezing (80%). Only 36.1% had fever and 8.3% cyanosis. The mild form of the disease was present in 30.6% and the moderate form in 69.4%. Conclusions: The most frequent epidemiological characteristics were male sex, age less than 6 months, adequate weight at birth, term and eutrophic. The most frequent clinical features were tachypnea, retractions, wheezing and cough. The mild form of the disease was the most frequent.